Input Subsidy Programs in Developing Countries: Lessons from an Asia/Africa Comparison - Rashid, Shahidur (2013)
IFPRI Policy Seminar "Input Subsidy Programs in Developing Countries What Works, What Doesn’t, and Why?" presentation by Shahidur Rashid, IFPRI, on 18 April 2013.